Phytochemical studies on goniothalamus woodii - Fasihuddin , B. A.; Laily B. Din; Zuriati Zakaria (Universiti Kebangsaan Malaysia, 1996)
Three compounds were isolated and characterized from the roots of Goniothalamus woodii. Based on their spectroscopic data, the compounds were identified as goniothalamin, 5-acetoxygoniothalamin and goniotriol.